A república nos livros didáticos de história da era Vargas (1938-1945) - Wendt, Wanessa Tag (2015)
Throughout this paper we sought to identify and analyze, specifically, how the republic is represented by seven authors - Alfredo Gomes, Basílio de Magalhães, Hélio Vianna, João Pereira Vitória, Joaquim Silva, Jonathas Serrano, Mário Sette – in their history textbook for high school students. The books were published during the Vargas Period, more specifically between the first teaching reform, for that level in 1931, and the after the CNLD creation in 1938 until the end of the regime in 1945. For that purpose, in the first moment, we mapped the educational model implanted by the Vargas regime and we highlighted the history teaching definitions for high school students through CPDOC documents. The CNDL creation in 1938 was also the object of discussion as well as the establishment of specific rules to make and authorize those textbooks that circulated in the Brazilian schools in that moment. Those questions, that were part of Vargas nationalist project, had influence directly the creation of those materials. Therefore, for the second part of this paper, we investigated how those seven authors that produced the high school materials made for history teaching adapted themselves to the state rules and how they represented in their textbooks the two republican periods: the first republic (1889 – 1930) and the second republic which begins in 1930. For this purpose we use discursive textual analyses methodology. (MORAES, p. 2003; 2011).